Detection roasting level of Lintong coffee beans by using euclidean distance - Yohanssen Pratama; I Gde Eka Dirgayussa; Paian Fernando Simarmata; Mia Hotmaria Tambunan (Bulletin of Electrical Engineering and Informatics, 2021)
Coffee roasting is the process by which raw coffee beans (green beans) are roasted until they reach a certain roast level. In general, the roast level of roasted coffee beans is divided into 3 levels, namely the roast level of light, medium and dark. One way to find out the roast level of roasted coffee beans is to see the color change of the coffee beans. However, it is very difficult to know the exact color conditions of each roast level of roasted coffee beans and this can be overcome by build an automatic coffee roasting equipment. In this research, an automatic coffee roaster was done with a system that is able to control the roasting temperature and stirring of coffee beans. This tool can also monitor the change in color of the coffee beans during the roasting process. The system that has been implemented can detect color changes and classify the level of dark roast of roasted coffee beans using the Euclidean distance algorithm. The Euclidean distance give a threshold to classified the roast level. The system accuracy for predicting coffee beans color at the level of dark roast is 90% and 80% for overall.